ZmCCA1a on Chromosome 10 of Maize Delays Flowering of Arabidopsis thaliana - Shi, Yong; Zhao, Xiyong; Guo, Sha; Dong, Shifeng; Wen, Yanpeng; Han, Zanping; Jin, Weihuan; Chen, Yanhui (Frontiers in Plant Science, 2020)
Maize (Zea mays) is a major cereal that originated from low latitude zones, thus photoperiod sensitivity is one of the most important barriers for the use of tropical/subtropical germplasm in temperate regions. However, studies into the mechanisms underlying circadian regulation in maize are just at the beginning. We cloned ZmCCA1 on chromosome 10, which is a homolog of AtCCA1/AtLHY, by map-based cloning. The Myb domain of the deduced amino acid sequence of ZmCCA1 shared high similarity with the Myb domain sequences of AtCCA1/AtLHY and ZmLHY (another homolog of AtCCA1/AtLHY mapped on chromosome 4 in maize); however, the C-terminal sequences were highly variable. Transiently or constitutively expressed ZmCCA1-YFP localized to the nuclei of several plant cell systems. Unlike AtCCA1 and AtLHY, ZmCCA1 did not form a homodimer or interact with ZmLHY. Transcripts of ZmCCA1 showed circadian rhythm and peak expression around sunrise in maize inbred lines CML288 (photoperiod sensitive) and HZ4 (photoperiod insensitive). Under short-day conditions the expression of ZmCCA1 in CML288 and HZ4 was repressed compared with under long-day conditions, but the effect on its expression in HZ4 was mild. Overexpression of ZmCCA1 in Arabidopsis thaliana delayed flowering under the long-day condition, but the length of hypocotyl was not affected under short-day and constant dark conditions. In addition, expression of endogenous AtCCA1/AtLHY and the downstream genes AtGI, AtCO, and AtFt was repressed in ZmCCA1-overexpressing seedlings. Our results suggest that the function of ZmCCA1 is similar, at least in part, to the function of AtCCA1/AtLHY and ZmLHY, implying that ZmCCA1 may be a major component of the circadian clock pathway in maize.